2014
DOI: 10.1007/s00190-014-0705-0
|View full text |Cite
|
Sign up to set email alerts
|

High tilt susceptibility of the Scintrex CG-5 relative gravimeters

Abstract: We report on the susceptibility of the Scintrex CG-5 relative gravimeters to tilting, that is the tendency of the instrument of provide incorrect readings after being tilted (even by small angles) for a moderate period of time. Tilting of the instrument can occur when in transit between sites usually on the backseat of a car even using the specially designed transport case. Based on a series of experiments with different instruments, we demonstrate that the readings may be offset by tens of µGal. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…Such effect, reported by Reudink et al . (), is also confirmed by preliminary test measurements with gravimeters 4372 and 4373. Although hysteresis effect is specific for each gravimeter, it also depends on conditions during transport.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…Such effect, reported by Reudink et al . (), is also confirmed by preliminary test measurements with gravimeters 4372 and 4373. Although hysteresis effect is specific for each gravimeter, it also depends on conditions during transport.…”
Section: Resultssupporting
confidence: 67%
“…Furthermore, if a gravimeter is left stationary off level, this can only cause a decrease in the tension of the spring (since only a portion of gravity affects a sensor) and consequently increases hysteresis. Such effect, reported by Reudink et al (2014), is also confirmed by preliminary test measurements with gravimeters 4372 and 4373. Although hysteresis effect is specific for each gravimeter, it also depends on conditions during transport.…”
Section: O N C L U S I O Nsupporting
confidence: 73%
See 2 more Smart Citations
“…The CG-5 shows a repeatability in the order of˙0.03 mGal. This value seems to be a little higher than other measurements with this instrument but is explainable by some remaining hysteresis effects (Reudink et al 2014) and some difficulties in estimating the drift parameters out of the data of one single day only. In the combined solution of the CG-5 measurements the residuals are usually smaller than 0.015 mGal and the drift parameters for each day get more consistent.…”
Section: Comparisons Of the Measurements Of 2013mentioning
confidence: 94%